Space configurations for empowering university-community interactions - Dorland, Jens; Clausen, Christian; Jørgensen, Michael Søgaard (Science and Public Policy, 2019)
Some see universities as a possible source of solutions to enable a sustainable transition and overcome societal challenges. Findings from three multisite case studies of Desis Labs, FabLabs, and Science Shops shed light on how universities can help empower communities and solve societal challenges locally. Adopting a sociotechnical and flat relational perspective inspired by science and technology studies (STS), we focus on the material and spatial aspects of how these spaces are configured, thereby ensuring practical relevance for policy makers and practitioners. Applying an analytical generalization methodology, we condense the qualitative data into a typology of three ideal space-types (i.e. affording, mediating, and impact-oriented) that represent specific configurations of actors, researchers, students, communities, spaces, infrastructure, equipment, facilitators, etc. The ideal space-types empower communities in different ways, require different resources to create and operate, and translate differently into specific local contexts.
Number: 5
Keywords: Communauté d'innovation; Laboratoire vivant; Méthodes; Réservé UdeM; Rôle des universités; Université